STUDY OF THE DISCHARGE AND THE FLOOD WATER LEVEL OF MEREUBO RIVER, WEST ACEH REGENCY - ZULFIKAR (NIM 95005316); Pembimbing: Joko Nugroho, ST, MT, Ph.D., RADIA
West Aceh as one of agriculture development area in Nanggroe Aceh Darussalam Province is hardly supported by several watersheds with big water discharge potency, high rainfall and big vast potency of agriculture expansion area. Meureubo River which flows cross over Meulaboh city, the capital of West Acheh regency, at part of its downstream besides supplies water for creature activity, also reduces flood hazard which often happens every year. Meureubo River with watershed about 1.885 km2 and main river length 148 kilometers has steep topography at the upstream of watershed and at its downstream which is relatively flat, represents the lowland and dangerous toward the flood. The modeling of Meureubo River along 17,54 kilometers from estuary and the flood simulation by using HEC-RAS version 3.1.3 have produce the peak discharge of river outlet in the amount 1.780 m3/s for return period 10years. Flood reduction scenario with implementation about 20 Ha of storage area reduces the peak discharge for return period 10 years becomes 1.681 m3/s. Derivation of average flood water level is about 14,4 cm or 2,7 percent from existing condition of flood water level. This scenario is not significant for flood reducer. Nevertheless the storage area could be maintained as temporary retention area before flown back to river. Flood reduction scenario with implementation about 20 Ha of storage area and the embankment at distance 70 m from bank station point reduces the peak discharge for return period 10 years down to 1.698 m3/s. implementation of this scenario can be recommended to reduce the flood. The influence radius of floodplain should be defended at 70 meters from the point of river bank station.